Role of Ayurveda in Trichomonas Vaginitis- A Case Report. - Tiwari, Sneha; Patel, Jalpa D (International Research Journal of Ayurveda & Yoga, 2023)
Health of a woman plays a very important role in family which reflects on society too. Most women suffer with vaginal infection; among them Trichomonas vaginitis is very common. Though it is projected to be 40 to 50% in the age group of childbearing women, the incidence of trichomonas infection is about 10-15%. The inflammation and itching at the site of the vulva and vagina indicate the sign of probably of trichomonas vaginitis. Methodology: In this present case study, Patient age 47 year came to OPD with complaint of pain lower abdomen off and on since 2 yrs , pt had no other symptom . On basis of these complaints along with P/A examination, P/V and P/S examination have been done, which reveals trichomonas infection. She was supposed to be treated with traditional ayurvedic formulations; the case was treated for 7 days with a combination of different traditional Ayurvedic drugs, and sthanik chikitsa with the goal of relieving symptoms and curing the disease. This patient was treated with traditional Ayurvedic formulations like Triphala Guggulu, Chandraprabha Vati, Gandhak Rasayana, Sthanik Chikitsa - Yoni Dhawana (Vaginal douche) with Panchvalkala Kwatha followed by Yoni Pichu with Jatyadi Taila once in a day for 7 days. Result: Only traditional Ayurvedic medicines were used during the course of the treatment. Follow-up showed complete disappearance of strawberry appearance of cervix and symptoms also subsided to a great extent. Discussion: The present study emphasizes the role of Ayurveda in bringing a positive result in the management of Trichomonas vaginitis